Newton’s Law Practicum Enhancing Science Motivation and Learning : Praktikum Hukum Newton Meningkatkan Motivasi dan Pembelajaran Sains - Akmal, Dita Aurellia; Efendi, Nur (Inquest Journal, 2024)
This correlational study investigates the relationships among students' perceptions of Newton's Law practicum, learning motivation, and cognitive learning outcomes in science education. Utilizing quantitative methods and questionnaire surveys, data were collected from VIII grade students. The findings reveal significant but weak correlations: students' perceptions of the Newton's Law practicum correlate positively with cognitive learning outcomes, as does learning motivation. Additionally, a positive relationship exists between students' perceptions of the practicum and their learning motivation. These results underscore the importance of both pedagogical practices and student motivation in enhancing cognitive learning outcomes in science education, suggesting implications for instructional design and educational policy aimed at fostering effective science learning environments.